Heterogeneous responses to school track choice: Evidence from the repeal of binding track recommendations - Maximilian Bach (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
This paper studies heterogeneity in schooling decisions by socio-economic status (SES) in response to a repeal of achievement-based admissions requirements (i.e. binding track recommendations) in Germany's between-school tracking system. The main contribution is to show that while previously ineligible high-SES students are relatively more likely to enroll in the highest (academic) track than comparable low-SES students after the repeal, the SES gap in academic track enrollment does not increase. The reason is that low-SES students, who were already eligible for the academic track before the repeal, increase their probability of enrolling in the academic track. A key mechanism driving low-SES students' response appears to be lower preferences for the intermediate track due to concerns about the inflow of mostly low-achieving and low-SES students from the lowest (basic) track after the repeal.
Keywords: I24; I28; J24; J62; 330; education; school choice; intergenerational mobility; inequality of opportunity; tracking